INVESTIGATION OF RAINFALL ANOMALIES RELATED TO SEA BREEZE INFLUENCE IN JUNE JULY AUGUST 2022 IN NORTH HALMAHERA - Sabrina, Vina
Rainfall events in the June-July-August (JJA) 2022 period in the North Halmahera region are often not well predicted in regional scale weather forecast models. This is thought to be due to the influence of local circulation that can cause rain to occur during this period. A local phenomenon that can affect weather dynamics in coastal areas is the Sea Breeze Circulation (SBC). In previous research, it is known that there are differences in spatial patterns of rainfall around the coast of large islands and small islands whose diurnal patterns of rainfall are influenced by SBC. On large islands, the maximum rain intensity occurs in mountainous areas, while on small islands it occurs in the center of the island. This is in accordance with the topography and morphology of the coastline of North Halmahera. In this study, analysis of climatological and synoptic conditions using reanalysis data and analysis of observational data from stations near the coast and inside the island to prove that rainfall events in JJA 2022 are influenced by local factors. Then verification of model output data with meteorological station observation data is carried out by spatial comparison of model output data and radar observation data, comparison of diurnal parameter values and through statistical calculations using the Root Mean Square Error (RMSE) method to measure the ability of the model to predict weather. The final stage is to simulate the atmospheric phenomena and meteorological conditions using the Weather Research and Forecasting (WRF) model with a three-domain downscaling method to increase the resolution of the model output in order to reveal the dynamics of the rainfall process and its relationship with topography and SBC in that period. The results showed that climatological conditions in that period had a decreased average rainfall, but there was still the potential for convective activity, weak synoptic wind flow but unstable atmospheric conditions and the potential to increase convective activity. Based on the observation results, there are rainfall anomalies in several rainy day samples compared to the average rainfall conditions in the JJA 2022 period. In the rainy day sample used, there was a change in meteorological paremeter conditions in the form of a decrease in surface air temperature, an increase in relative humidity and an increase in wind speed indicating the influence of SBC. The verification results show that the WRF model with increased resolution is able to simulate weather conditions in the 2022 JJA period well in describing diurnal variations in various weather parameters and in describing their spatial patterns. The model output results show that the rain that occurred in the JJA 2022 period was caused by the influence of topography on SBC. In the morning the coastal area is still influenced v by land winds, when the land warms up the sea breeze begins to propagate into the island and causes changes in meteorological conditions such as an increase in mixing ratio, rainfall, decrease in relative humidity and surface air temperature. The heaviest rainfall occurs in the center of the island near the mountains. This is due to the presence of topography that causes air mass to be retained. The existence of complex topography in the North Halmahera region in the form of topographic variations plays a role in inhibiting SBC propagation which causes the formation of konvergensi angin laut after SBC passes through the mountains, the existence of konvergensi angin laut forms deep convection over the mountains which is characterized by the presence of a thick moist layer over the mountains and produces rain. The morphological complexity of the coastline in this case the existence of bays and islands close to the island of Halmahera causes the wind flow to diverge in the eastern part of North Halmahera and drives convergence in the North. Therefore, SBC can be used as a consider material in the preparation for weather forecasting and early warning of extreme weather in the North Halmahera region, especially in the JJA period.